Immobilization of Residual Basic Dyes onto Polyamide Ion-Exchanger Materials - Mohamed Hassen V Baouab; Mohamed Khalfaoui; Aghleb Bartegi; Robert Gauthier (Adsorption Science & Technology)
This paper reports the preparation of methacrylic acid-grafted nylon (MAA—nylon) by treating nylon-6,6 fibres with methacrylic acid (MAA) and the use of this modified polyamide as an ion-exchanger for the immobilization of pollutant basic dyes. The grafting of MAA onto nylon-6,6 was demonstrated both by weight uptake and atomic force microscopy. The exchange capacity of MAA—nylon was evaluated by potentiometric titration of the acidic groups. Five MAA—nylon fibres with different degrees of grafting (20–80%) were tested for the adsorption of two basic dyes, viz. Basic Blue 3 and Basic Red 24. Such adsorption was monitored by visible spectroscopy. The adsorption capacity was found to depend on the degree of grafting and on the temperature. The experimental data were fitted using the Langmuir and Freundlich models. However, an improved fit could be obtained by using the Jossens model.